ARTIFICIAL INTELLIGENCE IN EDUCATION (Journal of Universal Science Research, 2025)
The COVID-19 pandemic has accelerated the integration of online and hybrid teaching strategies. Educators began adopting artificial intelligence (AI) tools to support student learning outcomes. However, these technologies were unfamiliar to many, highlighting a need for teachers to acquire digital competencies that align with AI integration.This study discusses the challenges and possibilities presented by AI in education.